Variabilidad de los factores de calidad para el corcho en plancha. (II Congreso Forestal Español, 1997)
Main parameters affecting cork production and quality (thickness, apparent density, surface density, annual growth and porosity) are studied. Data from a sample of 105 pieces of cork (20 cm x 20 cm size) collected in seven different sites are analysed. Sites are considered as representative of the most common Spanish Quercus suber stands. Means and standard deviations of this parameters are presented for the different quality grades obtained by manual classification, focusing on the effect of grading on porosity and density. The effect of site factor on density and annual growth is also studied.